YouTube for Academics: Exploring Learning Habits of Post Graduate Students - Singh, Dev Vrat; Gourav Hota (Journal of Advanced Research in Journalism & Mass Communication, 2021)
The digital revolution has transformed the entire ecosystem of higher education across the globe during the last one decade. The changes emerged out more visibly during the pandemic times. But how far the social media platforms like YouTube have been effectively adopted by the students and teachers is yet to be studied systematically. This is interesting to know how the stakeholders of the traditional education system have been negotiating with the new technological innovations. By doing an opinion survey of 107 post graduate students of a central university and experience survey of 10 teachers, this study has attempted to answer few research questions related to the usages of YouTube for higher education. The study argues that students do watch YouTube videos frequently and abundantly for learning various concepts and processes related to the syllabus. Whereas, teachers watch YouTube videos to get new inputs during the preparation for lectures and for quick revision of the topic. However, teachers believe that YouTube is responsible for lack of attentiveness and attendance of students in the classrooms. Moreover, teachers also warn that excessive dependency of students upon YouTube videos for examination preparations result in shallow and limited understanding of the subject. How to cite this article: Hota G, Singh DV. YouTube for Academics: Exploring Learning Habits of Post Graduate Students. J Adv Res Jrnl Mass Comm 2021; 8(1): 23-32.